The Implementation of Leasing Bengkok Land and Its Legal Consequences - Rizal, Fiki Apriliawan (Jurnal Konstatering, 2023)
This research was motivated by the renting of crooked land in Pecangaan District, Jepara Regency which was carried out by the Village Head and Village Apparatus with an open auction with the community. The empirical juridical approach is used in this study, used to analyze various laws and regulations in the agrarian sector. The result of this research is that the village head takes legal action, namely the implementation of the village land lease is correct with an open auction procedure to the community. The implementation of the rent of the crooked land is correct, in accordance with laws and regulations, and produces benefits for the village and the community. The lease agreement made before a notary is then set forth in the form of a deed. In principle, every legal act must adhere to the principle of Nemo plus juris. Dispute resolution if the parties are by default can be resolved by deliberation, and if the deliberation is not reached, it is resolved through a general court. Keywords: Dispute; Land; Resolution.